The Effect Of Public Speaking Experience And Self-Confidence On The Verbal Communication Skills Of Office Administration Education Students Enrolled In 2023 At Medan State University - Aisyah; Alfi Nura (CV Putra Publisher, 2026)
This study aims to determine the influence of public speaking experience and self-confidence on the verbal communication skills of students in the Office Administration Education Program, Class of 2023, at the State University of Medan. This study employs a quantitative approach using an ex post facto method. The study population consists of 69 students, and the entire population was selected as the sample using total sampling. Data were collected through questionnaires and documentation. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results indicate that public speaking experience has a positive and significant effect on students’ verbal communication skills, with a calculated t-value of 5.639 and a significance level of 0.000. Self-confidence also has a positive and significant effect on students’ verbal communication skills, with a calculated t-value of 4.630 and a significance level of 0.000. Simultaneously, public speaking experience and self-confidence have a positive and significant effect on students’ verbal communication skills, with a calculated F-value of 161.489 and a significance level of 0.000. The coefficient of determination of 0.830 indicates that public speaking experience and self-confidence account for 83% of the variation in students’ verbal communication skills, while the remaining 17% is influenced by other factors outside the scope of this study. The implications of this study suggest that improving students’ verbal communication skills can be achieved by providing broader opportunities for public speaking practice and by building self-confidence through presentations, discussions, seminars, and other academic activities that support public speaking skills.